Two distinct patterns of Clostridium difficile diversity across Europe indicates contrasting routes of spread - Eyre, D; Davies, K; Davis, G; Fawley, W; Dingle, K; De Maio, N; Karas, A; Crook, D; Peto, T; Walker, A; Wilcox, M (Oxford University Press, 2018)
Background Rates of Clostridium difficile infection vary widely across Europe, as do prevalent ribotypes. The extent of Europe-wide diversity within each ribotype is however unknown. Methods Inpatient diarrhoeal faecal samples submitted on one day in summer and winter (2012-2013) to laboratories in 482 European hospitals were cultured for C. difficile, and isolates ribotyped; those from the 10 most prevalent ribotypes were Illumina whole-genome sequenced. Pairwise single nucleotide differences (SNPs) were obtained from recombination-corrected maximum-likelihood phylogenies. Within each ribotype, country-based sequence clustering was assessed using the ratio of the median SNPs between isolates within versus across different countries using permutation tests. Time-scaled Bayesian phylogenies where used to reconstruct the historic location of each lineage. Results Sequenced isolates (n=624) were from 19 countries. Five ribotypes had within-country clustering: ribotype-356, only in Italy; ribotype-018, predominantly in Italy; ribotype-176, with distinct Czech and German clades; ribotype-001/072, including distinct German, Slovakian, and Spanish clades; and ribotype-027, with multiple predominantly country-specific clades including in Hungary, Italy, Germany, Romania and Poland. By contrast, we found no within-country clustering for ribotypes 078, 015, 002, 014, and 020, consistent with a Europe-wide distribution. Fluoroquinolone-resistance was significantly more common in within-country clustered ribotypes (p=0.009). Fluoroquinolone-resistant isolates were also more tightly geographically clustered, median (IQR) 43 (0-213) miles between each isolate and the most closely genetically-related isolate vs. 421 (204-680) in non-resistant pairs (p<0.001). Conclusions Two distinct patterns of C. difficile ribotype spread were observed, consistent with either predominantly healthcare-associated acquisition or Europe-wide dissemination via other routes/sources, e.g. the food chain.